Natural fibres : alternative fibres for polymer composites. - Salit, Mohd Sapuan (2012)
This paper reviews natural fibres used as reinforcements for polymer composites in Malaysia. Oil palm, sugar palm, pineapple leaf, coir, coconut shell, rice husk, banana pseudostem, kenaf, rubber wood, bagasse and bamboo are reported to be used either in the forms of fibres or fillers in synthetic and biopolymer composites. Natural fibre reinforced polymer composites are potentially used in industries such as automotive, furniture and building construction industries and a move to use them in aerospace industry is being studied.